The Diversity and habitat use by birds in urban gradients in the city of Guayaquil, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2015)
This research establishes the biological diversity and habitat preference of bird communities in 16 places in the city of Guayaquil, within three differents gradients: urban, suburban and periurban. A total of 116 species were identified; the more abundant were Columba livia, Columbina buckleyi, and Thraupis episcopus. Of the total species recorded, 41% have been found in the urban and 78% in the periurban areas, respectively. Using the Shannon index, the highest record (3.89) has been found in the suburban gradient, and the lowest (2.57) in the urban gradient. The medium between the index of diversity and urban gradient was p = 0.03, that means a significant difference. The canopy is the most widely used habitat; although there is a clear trend for the use of open spaces in the urban gradient and airspaces in the periurban gradient. The results show that the bird richness decrease while the urban gradient increases, and also suggest that it is necessary to have many types of habitats in the city in order to conserve a higher richness of birds.
Keywords: Anthropization; birds; diversity; Ecuador; Guayaquil; urbanization